2012
DOI: 10.5433/1679-0359.2012v33n1p193
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of neem oil nanoformulations to Bemisia tabaci (GENN.) Biotype B (Hemiptera: Aleyrodidae)

Abstract: The nanotechnology, through encapsulation of active ingredients, has showed an important way to avoid problems with quickly degradation of the pesticide molecules. Thus, neem (Azadirachta indica) oil nanoformulations containing β-ciclodextrin and poli-ε-caprolactone (PCL) were tested as to their control efficiency against eggs and nymphs of Bemisia tabaci (Genn.) biotype B reared in soybean. The Lethal Concentration (LC 50 ) was estimated using a commercial neem oil (Organic Neem ® ) on firstinstar nymphs to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 15 publications
1
11
0
7
Order By: Relevance
“…Por meio de aplicação foliar, Carvalho et al (2012) estimaram uma CL 50 de 1,6 mg de azadiractina L -1 para ninfas de B. tabaci biótico B a partir de uma formulação comercial à base de óleo de nim (Organic Neem  ), valor muito inferior ao verificado no presente estudo. Além das diferenças qualitativas e quantitativas das formulações testadas em ambos os estudos (especialmente a ocorrência e o teor de compostos ativos minoritários), a capacidade de sorção dos compostos ativos no substrato, ou mesmo o tempo necessário para translocação até os folíolos do terço superior do tomateiro, sítio preferencial de oviposição e alimentação de B. tabaci biótipo B (Toscano et al, 2002), pode explicar tais diferenças nas CLs estimadas para as duas formas de aplicação do nim.…”
Section: Resultsunclassified
“…Por meio de aplicação foliar, Carvalho et al (2012) estimaram uma CL 50 de 1,6 mg de azadiractina L -1 para ninfas de B. tabaci biótico B a partir de uma formulação comercial à base de óleo de nim (Organic Neem  ), valor muito inferior ao verificado no presente estudo. Além das diferenças qualitativas e quantitativas das formulações testadas em ambos os estudos (especialmente a ocorrência e o teor de compostos ativos minoritários), a capacidade de sorção dos compostos ativos no substrato, ou mesmo o tempo necessário para translocação até os folíolos do terço superior do tomateiro, sítio preferencial de oviposição e alimentação de B. tabaci biótipo B (Toscano et al, 2002), pode explicar tais diferenças nas CLs estimadas para as duas formas de aplicação do nim.…”
Section: Resultsunclassified
“…Synthesized Ni NPs were subjected to pesticidal activity against agricultural pest Callasobruchus maculates which resulted in 97.31% mortality. The results not coincidence with Carvalho et al (2012) who tested perimented neem (Azadirachta indica) oil in nano formulations containing betaciclodextrin and poli-epsilon -caprolactone (PCL) against eggs and nymphs of Bemisia tabaci (Genn.) and indicated that the nano formulations were less efficient to control the B. tabaci biotype B nymphs than the commercial neem oil.…”
Section: Determination Of Lc 50 Of Tested Agnps-eos Against Female Ofmentioning
confidence: 69%
“…Due its high potential as a green biocide, the neem extracts were already used to create controlled-release systems by using carbohydrates (b-cyclodextrin, starch and alginate) (Carvalho et al, 2012;Jerobin et al, 2012) and biodegradable polymers (polycaprolactone and polyhydroxybutyrate) (De Carvalho et al, 2015;Forim et al, 2013) as shell materials of nano/microcapsules; however, the high water retaining of these materials may accelerate the hydrolysis and release of neem compounds.…”
Section: Introductionmentioning
confidence: 99%